2001
DOI: 10.1523/jneurosci.21-22-08931.2001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Deafness and Early Exposure to Sign Language on the Cerebral Organization for Motion Processing

Abstract: This functional magnetic resonance imaging study investigated the impact of early auditory deprivation and/or use of a visuospatial language [American sign language (ASL)] on the organization of neural systems important in visual motion processing by comparing hearing controls with deaf and hearing native signers. Participants monitored moving flowfields under different conditions of spatial and featural attention. Recruitment of the motion-selective area MT-MST in hearing controls was observed to be greater w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
243
2
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(274 citation statements)
references
References 43 publications
21
243
2
8
Order By: Relevance
“…These data are consistent with observations that, despite auditory deprivation, deaf signers show activity within classical auditory regions in response to visual linguistic stimuli (Petitto et al, 2000;Bavelier et al, 2001;Emmorey et al, 2002;MacSweeney et al, 2002;Fine et al, 2005). Brain imaging studies of signers have reported robust right hemisphere perisylvian activation for signing Bavelier et al, 2001;MacSweeney et al, 2004;Newman et al, 2002). The present data, which uses individual sign stimuli, show little evidence of right perisylvian activation when contrasted against our baseline task ( Figure 3c, Table 1c, right panel) and in the direct contrast to non-linguistic gestures ( Figure 5, Table 5, left panel).…”
Section: Deaf Signerssupporting
confidence: 90%
“…These data are consistent with observations that, despite auditory deprivation, deaf signers show activity within classical auditory regions in response to visual linguistic stimuli (Petitto et al, 2000;Bavelier et al, 2001;Emmorey et al, 2002;MacSweeney et al, 2002;Fine et al, 2005). Brain imaging studies of signers have reported robust right hemisphere perisylvian activation for signing Bavelier et al, 2001;MacSweeney et al, 2004;Newman et al, 2002). The present data, which uses individual sign stimuli, show little evidence of right perisylvian activation when contrasted against our baseline task ( Figure 3c, Table 1c, right panel) and in the direct contrast to non-linguistic gestures ( Figure 5, Table 5, left panel).…”
Section: Deaf Signerssupporting
confidence: 90%
“…Even in a case in which the auditory cortex of DS is more responsive to any visual stimulation, this effect could be driven by a top-down mechanism developed with language experience. Another strategy has been to use hearing native signers (hearing children of deaf parents) as controls 8,[13][14][15] . With that comparison it is difficult to be conclusive about whether an effect arises from deafness or from different language experience.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse âmbito, Bavelier et al (2001) referiram que a condição desses ouvintes bilíngues bimodais é consequência da aquisição simultânea de duas línguas: a de sinais, pelas interações linguísticas entre os familiares, e a oral, pela convivência com a comunidade ouvinte. , Emmorey e McCullough (2009) e MacSweeney et al (2002b) sugeriram que tal condição possa interferir na organização cerebral das línguas.…”
Section: áReas Brodmann Voxelsunclassified